Rheological Study of the Solidification of Photopolymer and Dispersed Nanotube Systems - Darsono Nono; Mizunuma Hiroshi; Obara Hiromichi (Applied Rheology, 2011)
We herein describe a set of rheological measurements that were carried out in order to characterize the solidification of photopolymers. The solidification depends on the length of time of exposure to UV light, and the intensity of that light, which reduces with distance from the irradiative surface. Liquid prepolymer was solidified inside the gap of a parallel disk rheometer by irradiation of the prepolymer with UV light through a fixed quartz disk. The rheological time-dependent changes were measured and analyzed for both unidirectional and oscillatory shear. The results were compared with those obtained by direct measurement in the absence of shear. When the thickness of the sample was less than 0.1 mm, the analysis for unidirectional shear flow yielded a reasonable agreement for both critical exposure and solidified depth. When the thickness was greater than 0.1 mm, the application of unidirectional shear delayed the start of the solidification but then caused it to occur more rapidly. This dependence of the solidification on the thickness of the sample was more significant for dispersed systems of nanotubes and for dynamic measurements made under oscillatory shear. The increase in viscosity due to photopolymerization was also estimated, and its effect was discussed.